Implementasi K-Means Clustering Dalam Pengelompokkan Banyaknya Jumlah Petani Berdasarkan Kecamatan di Provinsi Jawa Barat - Muhammad Yamin Nurzaman (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Farmers play a crucial role in addressing climate change and the global food crisis, but they must adapt to the changing agricultural production system. To help the West Java Provincial Agriculture Service prepare effective farmer empowerment programs, K-Means Clustering can be used to classify farmers in the province based on sub-districts. This research aims to group sub-districts according to their farmer population, and the clustering process has produced two clusters, with the highest cluster comprising 22,120 people.